Analisis Kesulitan Belajar Matematika Pada Materi Operasi Hitung Perkalian Dan Pembagian Siswa Kelas IV SDN 193 Pekanbaru - Rizki Damayanti; Siti Quratul Ain (Jurnal Penelitian Ilmu Pendidikan Indonesia, 2023)
Learning difficulties are disorders that result in a lack of motivation to complete tasks, difficulties in understanding learning principles, and difficulty understanding learning concepts. The purpose of this research is to: 1) analyze the difficulties of learning mathematics in the material on arithmetic operations, multiplication, and division in class IV. 2.) Analyze the factors that can influence the difficulty of learning mathematics in class IV multiplication and division arithmetic operations material. This research method uses descriptive qualitative research with data collection techniques, namely tests, observation, interviews, and documentation. The data analysis used was according to Miles and Huberman. The results of this research show that there are 3 forms of learning difficulties, namely: 1) students' difficulty understanding the concept; 2) students' difficulties in using principles; and 3) students' difficulties in solving verbal problems. Internal factors such as students who are lazy when studying and low student motivation to learn cause students to lack enthusiasm for learning and lack curiosity. External factors such as: 1) The school environment is clean, but the classrooms are so exposed to sunlight that it is difficult to see the blackboard. 2). Complete facilities and infrastructure are rarely used when studying.